Four steps to identify mechanisms of ICT4D: A critical realism‐based methodology. Issue 6 (24th September 2018) - Thapa, Devinder; Omland, Hans Olav
Abstract: Questions such as 'What is ICT?' and 'What is development?' are relatively well‐answered and well‐documented in literature but work connecting the two has been limited. Existing ICT4D studies tend to be descriptive or prescriptive in nature, and hence the explanation of how and why ICT works in the contexts of developing countries needs further investigation. ICT cannot by itself lead to development: it has to be deployed by actors in a given social, political, cultural, and technical context, under conditions at the time of deployment. The interplay of the above‐mentioned elements in any given development situation relies on underlying mechanisms that may explain how and why ICT leads to development. Therefore, it is important to investigate questions like "What mechanisms link ICT and development?" and "How do we identify these mechanisms?". To research and answer these questions, we propose a critical realism‐based four‐step methodological approach. The core idea of the critical realism‐based approach suggested in this study is to identify the underlying mechanism (s), particularly in ICT4D contexts, to explain how and why ICT leads to development. We illustrate the proposed methodology by applying it in a case study from Nepal.